Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]\ln(5-x) = \ln 5 - \ln x\\\\\implies \ln(5-x) + \ln x = \ln 5\\\\\implies \ln[(5-x)x] =\ln 5\\\\\implies \ln(5x -x^2) = \ln 5\\\\\implies 5x -x^2 = 5\\\\\implies x^2 -5x +5 =0\\\\\implies x = \dfrac{-(-5) \pm \sqrt{(-5)^2 - 4 \cdot 1 \cdot 5}}{2(1)}\\\\\implies x = \dfrac{5 \pm \sqrt{5}}{2}\\\\\text{Hence} ~x = \dfrac 12\left(5 + \sqrt 5\right)=3.62~~ \text{and}~~ x =\dfrac 12 \left(5-\sqrt 5\right) =1.38[/tex]
Answer:
x1 = 3.618, x2 = 1.382
Step-by-step explanation:
ln(5-x) = ln5 - lnx
ln(5-x) + ln(x) = ln5
ln(5x-x^2) = ln5
5x-x^2=5
0=x^2-5x+5
x = -(-5)±√((-5)²-4(1)(5)) / 2(1)
x = 5±√(25-20) / 2
x = 5±√5 / 2
x1 = 3.618, x2 = 1.382
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.